Analysis of Characteristics and Survival of Primary Cutaneous Adenoid Cystic Carcinoma of the Head and Neck. (January 2021) - Behbahani, Sara; Wassef, David W.; Povolotskiy, Roman; Pinto, Jessica; Joseph, Nia; Paskhover, Boris
Background/Objectives: Primary cutaneous adenoid cystic carcinoma (PCACC) is a rare skin tumor. The head and neck (H&N) is the most common anatomical location. Due to limited published cases, its clinical course and management are not well understood. Methods: The National Cancer Database (NCDB) was queried for all cases of H&N PCACC diagnosed from 2004 to 2016. Kaplan–Meier (KM) and Cox proportional hazards models were used to determine clinicopathological and treatment factors associated with survival outcomes. Results: A total of 201 cases were analyzed. The average age of diagnosis was 57.7 years (± SD 15.8). There was a female predilection (57.7%; P  < .05) with the most common primary site being the ear (58.2%). The average tumor size was 15.9 mm in diameter. The most common treatment was surgery alone (51.7%) with wide local excision being the common surgery performed (36.3%). 5-year and 10-year OS were 87.0% and 76.0%, respectively. A total of 65.8% of cases were localized (Stage I and II). KM analysis indicated that gender, age, insurance status, Charlson-Deyo Comobordity Score, and stage were significant predictors of OS ( P  < .05). Cox proportional hazards analysis revealed that patients with both private (HR 0.11, 95%CI [0.019-0.670]; P  = .02) and government (HR 0.12, 95%CI [0.019-0.972]; P  = .03) health insurance had a significantly decreased hazard of death than patients who were uninsured. Increasing age was associated with an increased hazard of death (HR 1.06, 95%CI [1.016-1.110]; P  = .01). Conclusion: This study represents the largest cohort of H&N PCACC studied to date and provides important clinicopathologic information for this rare tumor. Additionally, our results emphasize the importance of health insurance as an independent predictor of survival in PCACC.